2015
DOI: 10.1002/eqe.2609
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model of a deformable cantilever structure rocking on a rigid surface: experimental validation

Abstract: Summary This paper describes an experimental program to examine the dynamic response of deformable cantilevers rocking on a rigid surface. The primary goal of the tests is to verify and validate a dynamic rocking model that describes the behavior of these structures. The benchmark response data was obtained from shaking‐table tests on deformable rocking specimens with different natural vibration frequencies and different aspect ratios excited by analytical pulses and recorded ground motions. The responses comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 16 publications
5
96
0
4
Order By: Relevance
“…The change of pivot point is sometimes fast, but it is only scarcely instantaneous, as first observed by Srinivasan and Ruina (2008) and confirmed by Vassiliou et al (2017b). Figure 11 shows that 3D wobbling motion avoids the very large spikes in the moment time history that planar rocking structures experience (Oliveto et al, 2003;Acikgoz and DeJong, 2012;Truniger et al, 2015;Giouvanidis and Dimitrakopoulos, 2017b). Spikes do occur, at every fast (but not instantaneous) change of pivot point, but their magnitude is clearly smaller than the ones observed in planar motion and are always smaller than the moment strength of the pier (even when they are vectorially added), as shown in Figure 11.…”
Section: Rocking Piersmentioning
confidence: 62%
“…The change of pivot point is sometimes fast, but it is only scarcely instantaneous, as first observed by Srinivasan and Ruina (2008) and confirmed by Vassiliou et al (2017b). Figure 11 shows that 3D wobbling motion avoids the very large spikes in the moment time history that planar rocking structures experience (Oliveto et al, 2003;Acikgoz and DeJong, 2012;Truniger et al, 2015;Giouvanidis and Dimitrakopoulos, 2017b). Spikes do occur, at every fast (but not instantaneous) change of pivot point, but their magnitude is clearly smaller than the ones observed in planar motion and are always smaller than the moment strength of the pier (even when they are vectorially added), as shown in Figure 11.…”
Section: Rocking Piersmentioning
confidence: 62%
“…Many researchers have revisited the above assumption [23,25,35,[43][44][45] and formulated more detailed expressions. In this study the Housner coe cient of restitution will be used due to the following:…”
Section: Employed Numerical Modelmentioning
confidence: 99%
“…Researchers that have tried to experimentally validate Housner's model [20][21][22][23][24][25][26] have shown that, given the modelling uncertainty (especially of the one related to impact), it is di cult to confidently predict the time history response of a rocking block to a specific ground motion. Even if the coe cient of restitution is relatively well predicted, or determined via experiments, the response of the system to a ground motion is so sensitive that predicting the whole time history is practically impossible [27].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a simple freestanding rocking block has been systematically studied for more than five decades both when the block is assumed rigid [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and when it assumed deformable [27][28][29][30][31][32][33][34][35][36][37]. Small scale experiments have been also performed [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. It has been proven that structures that rock inplane (2d rocking) have remarkable dynamic stability.…”
Section: Introductionmentioning
confidence: 99%